2017
DOI: 10.1086/693473
|View full text |Cite
|
Sign up to set email alerts
|

Resemblance to the Enemy’s Eyes Underlies the Intimidating Effect of Eyespots

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Online enhancement: appendix.abstract: Eyespots of some prey are known to deter predators, but the reason for this response has not yet been established, and thus the taxonomically widespread occurrence of this color pattern has remained an evolutionary conundrum. Two alternative hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 44 publications
3
22
0
Order By: Relevance
“…More recently, however, Kjernsmo & Merilaita (2013) found that with artificial prey and predator-naive three-spined sticklebacks (Gasterosteus aculeatus), prey eyespots smaller than the predator fish's own eye very effectively deflected the attacks of sticklebacks. These same authors have since found that mimicry of predators' eyes through eyespot patterning can be key in evoking hesitation in attacks, as well as deflecting them, because predators associate those eyelike displays with their own enemies (Kjernsmo & Merilaita 2017). Marks of different shapes -including eyespots and eye stripes -seem to differ in their effectiveness at deflecting predators (Kjernsmo et al 2016), and undoubtedly we will learn more about the anti-predatory influence of fish patterning in future studies.…”
Section: Which Taxa Deflect Their Predators' Attacks and By What Mechmentioning
confidence: 95%
“…More recently, however, Kjernsmo & Merilaita (2013) found that with artificial prey and predator-naive three-spined sticklebacks (Gasterosteus aculeatus), prey eyespots smaller than the predator fish's own eye very effectively deflected the attacks of sticklebacks. These same authors have since found that mimicry of predators' eyes through eyespot patterning can be key in evoking hesitation in attacks, as well as deflecting them, because predators associate those eyelike displays with their own enemies (Kjernsmo & Merilaita 2017). Marks of different shapes -including eyespots and eye stripes -seem to differ in their effectiveness at deflecting predators (Kjernsmo et al 2016), and undoubtedly we will learn more about the anti-predatory influence of fish patterning in future studies.…”
Section: Which Taxa Deflect Their Predators' Attacks and By What Mechmentioning
confidence: 95%
“…Examples include the conspicuous underwings of Catacola moths (Sargent, 1990). Debate continues over whether circular spots function to startle predators or mimic the eyes of a larger predator (Stevens & Ruxton, 2014) but mounting evidence suggests that eye‐like markings can intimidate fish (Kjernsmo & Merilaita, 2017), that circular spots on butterfly wings prevent or delay an attack because of their resemblance to the eyes of bird predators (De Bona et al ., 2015), or because they elicit fear responses in predators (Olofsson et al ., 2012). We suspect that deimatic displays are likely to be more effective with larger markings and be used primarily against visually hunting predators.…”
Section: Individual Mechanismsmentioning
confidence: 99%
“…This location does not support the deflective function of eyespots since strikes would be directed towards the viscera or head. Therefore, eyespots in this location are more likely to be functioning through intimidation or predator mimicry (Kjernsmo and Merilaita 2017), or by making prey appear larger to gape‐limited predators (Mihalitsis and Bellwood 2017). By contrast, active species most often possess eyespots towards the posterior portion of the dorsal fin.…”
Section: Discussionmentioning
confidence: 99%